Analysis of Some Technological and Physical Characters of Mandarin (Citrus reticulata) Fruit in Iran. (28th April 2013) - Khadivi-Khub, Abdollah
Abstract : Knowledge of the physical properties of date fruit is necessary for the design of postharvesting equipment such as cleaning, sorting, grading, kernel removing, and packing. Also, the physical and mechanical properties are incorporated in the development of the grading machine as a case study. In this study, some physical and mechanical properties of three mandarin cultivars, as promising fruits, were analyzed to help the design of handling machines. According to results, the greatest dimensional characteristics were found for Page cultivar, whereas Onsho cultivar showed the lowest sphericity value (93%), and the highest sphericity was observed in Clementine cultivar (97%). The specific gravity of Page cultivar was 0/97, and this cultivar had the biggest fruit. Thus, it may be used for export. The volume measured was 1% higher than the calculated assumed shape of the spheroid ( V = 4.19 a 2 b ) . The relationship between diameters and mass was linear, and the correlation was high for all studied cultivars and mixed cultivar (combined all data). There was a linear relation between mass and volume of the mixed cultivar of mandarin with a high coefficient of determination.